1999
DOI: 10.1074/jbc.274.27.19041
|View full text |Cite
|
Sign up to set email alerts
|

Circular Permutation Analysis as a Method for Distinction of Functional Elements in the M20 Loop of Escherichia coliDihydrofolate Reductase

Abstract: A functional element of an enzyme can be defined as the smallest unit of the local peptide backbone of which the connectivity is crucial for the catalytic activity. In order to elucidate the distribution of functional elements in an active site flexible loop (the M20 loop) of Escherichia coli dihydrofolate reductase, systematic cleavage of main chain connectivity was performed using circular permutation. Our analysis is based on the assumption that a permutation within a functional element would significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The folding of the circularly permuted variants into functional proteins indicated that these variants can achieve a proper conformation for function and suggested that the amino acid sequence, and not the positioning of the N and C termini, determines the three-dimensional structure (28,30,31). Importantly, the identification of "functional elements," which have been defined as the smallest continuous sequences required for catalytic activity (23), makes possible the exploration of the "architecture of enzyme function." These functional elements, which are spread throughout the primary structure, define the functional active site in a properly folded enzyme (23).…”
Section: -Aminolevulinate Synthase (Alas)mentioning
confidence: 99%
See 3 more Smart Citations
“…The folding of the circularly permuted variants into functional proteins indicated that these variants can achieve a proper conformation for function and suggested that the amino acid sequence, and not the positioning of the N and C termini, determines the three-dimensional structure (28,30,31). Importantly, the identification of "functional elements," which have been defined as the smallest continuous sequences required for catalytic activity (23), makes possible the exploration of the "architecture of enzyme function." These functional elements, which are spread throughout the primary structure, define the functional active site in a properly folded enzyme (23).…”
Section: -Aminolevulinate Synthase (Alas)mentioning
confidence: 99%
“…Circular permutation, which disrupts the continuity of the polypeptide chain by placing the original N and C termini at new locations, has proved to be a valuable tool for studying the effects of polypeptide chain rearrangements on catalytic activity and folding of proteins (22,23). With circular permutation of proteins, the natural N and C termini are covalently linked, and new termini are created upon cleavage of the circularized protein at a different sequence position (24,25).…”
Section: -Aminolevulinate Synthase (Alas)mentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the effect of local structure of proteins on their susceptibility to unfolding by studying the import of CPs of DHFR. In these experiments, the original N and C termini of DHFR were connected by a short linker, new N termini were created at Pro-25 (CP P25) or Lys-38 (CP K38), and mitochondrial targeting sequences were fused to the proteins at the new N termini (26). The DHFR mutants have similar structures and stabilities and differ primarily in their topology (12).…”
Section: The Local Structure Adjacent To the Targeting Sequence Affectsmentioning
confidence: 99%